Ventral dermatitis in rowi (Apteryx rowi) due to cutaneous larval migrans. - Gartrell BD; Argilla L; Finlayson S; Gedye K; Gonzalez Argandona AK; Graham I; Howe L; Hunter S; Lenting B; Makan T; McInnes K; Michael S; et al. (Massey University, 2015)
The rowi is a critically endangered species of kiwi. Young birds on a crèche island showed loss of feathers from the ventral abdomen and a scurfy dermatitis of the abdominal skin and vent margin. Histology of skin biopsies identified cutaneous larval migrans, which was shown by molecular sequencing to be possibly from a species of Trichostrongylus as a cause of ventral dermatitis and occasional ulcerative vent dermatitis. The predisposing factors that led to this disease are suspected to be the novel exposure of the rowi to parasites from seabirds or marine mammals due to the island crèche and the limited management of roost boxes. This is the first instance of cutaneous larval migrans to be recorded in birds. Severe and fatal complications of the investigation resulted in the death of eight birds of aspergillosis and pulmonary complications associated with the use of bark as a substrate in hospital. Another bird died of renal failure during the period of hospitalisation despite oral and intravenous fluid therapy. The initiating cause of the renal failure was not determined. These complications have the potential to undermine the working relationship between wildlife veterinarians and conservation managers. This case highlights that intensive conservation management can result in increased opportunities for novel routes of cross-species pathogen transmission.
Keywords: 0502 Environmental Science and Management; 0603 Evolutionary Biology; 0605 Microbiology